Pianificare la mobilità urbana attraverso la cooperazione internazionale: l’esperienza del piano urbano della mobilità sostenibile di Herat - Mario Tartaglia (Geography Notebooks, 2019)
This paper deals with the planning process that led to the development of the Sustainable Urban Mobility Plan (SUMP) for the city of Herat, Afghanistan. Such planning experience is illustrated here with the aim of highlighting how the cooperative approach is applied to this case study, while trying to match the planning process to the local culture and to the essence of the Islamic city. If on one hand, the international cooperation brought a modern vision of urban mobility, aimed at increasing the levels of social, economic, and environmental sustainability, on the other hand the peculiarity of Herat’s urban context essentially influenced the planning process, for what concerned both methodology and results.